Signaling pathways involved in zymosan phagocytosis induced by two secreted phospholipases A2 isolated from Bothrops asper snake venom in macrophages - Zuliani, Juliana Pavan (2018)
Phagocytosis, a process involved in host defense, requires coordination of a variety of signaling reactions. MT-II, a catalytically-inactive Lys49-PLA2¸ and MT-III, an active Asp49-PLA2 isolated from Bothrops asper snake venom, activate phagocytosis in macrophages. In this study the signal pathways mediating zymosan phagocytosis, focusing in lipidic second messengers, were investigated. Macrophages collected from male Swiss mouse peritoneum were obtained 96 h after i.p. injection of thioglycollate. Phagocytosis was evaluated with non-opsonized zymosan in the presence or absence of specific inhibitors. Data showed that both venom PLA2s increased phagocytosis. Zileuton, Etoricoxib, PACOCF3 (5-LO, COX-2 and iPLA2 inhibitors, respectively), as well as WEB2170 (PAF receptor antagonist) significantly reduced phagocytosis induced by both venom PLA2s. However, Indomethacin (COX-1/COX-2 inhibitor) and Montelukast (CysL receptor antagonist) did not affect the toxins-induced phagocytosis. Moreover, while PACOCF3 (iPLA2 inhibitor), reduced the phagocytosis induced by MT-II and MT-III, AACOCF3 (cPLA2 inhibitor) significantly reduced the MT-II, but not MT-III-induced phagocytosis. These data suggest the effect of both sPLA2s depends on iPLA2 and that the effect of MT-II depends on activation of cPLA2. COX-2 and 5-LO-derived metabolites as well as PAF are involved in the signaling events required for phagocytosis induced by both venom sPLA2s.